The right to have rights citizenship, humanity, and international law - Kesby, Alison (Oxford : Oxford University Press, 2012)
Is it citizenship of a state or status as a human being that confers human rights on a person? And, if a person is stateless do human rights still apply to them? This book addresses these questions in the context of international human rights law and the notion of the 'right to have rights'.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Human rights; Citizenship